Pagiging lalaki, pagkalalaki, at pagkamaginoo - De Castro, Leonardo D. (1995)
Gender is often viewed as an inherent aspect of personal identity. But a gender-entrapped concept of identity engenders biases that could demean not only one gender or the other but humanity in general. An examination of various notions of masculinity in the Filipino context shows that characterizations of the genders are ambiguous save with respect to reproductive roles. Those characterizations are not compatible with ethically sound interpersonal relations. Respect for humanity requires a gender-neutral view of personal roles and responsibilities.
Keywords: Masculinity -- Philippines; Chivalry -- Philippines